3n-33n+90=0

Simple and best practice solution for 3n-33n+90=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-33n+90=0 equation:


Simplifying
3n + -33n + 90 = 0

Reorder the terms:
90 + 3n + -33n = 0

Combine like terms: 3n + -33n = -30n
90 + -30n = 0

Solving
90 + -30n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-90' to each side of the equation.
90 + -90 + -30n = 0 + -90

Combine like terms: 90 + -90 = 0
0 + -30n = 0 + -90
-30n = 0 + -90

Combine like terms: 0 + -90 = -90
-30n = -90

Divide each side by '-30'.
n = 3

Simplifying
n = 3

See similar equations:

| y^2-10y-4x+33=0 | | y^2-10y+4y+21=0 | | x^2+10x+4y+21=0 | | 28m(3)=3965 | | 65-4x=8x+15 | | 2x+20+4x-20=3x | | ln(-x)=0.111 | | 512x^3-1=0 | | 2x-x^2-10=0 | | 4j+60=400 | | -96=-6(x-15) | | 3(x+3)=2(4-x) | | 7x+2y-10x+5= | | 3(x-4)=2x-6 | | 12x(x-9)=0 | | 2(2x-3)=3(x-10) | | -5X+12=5X^2-12 | | N^3+n^2-6n=0 | | 14-7x=43-14x | | 2n^2+12n+15=-3 | | 2n^2+12n+15=3 | | 2n^2+n-120=0 | | 10x^2n+47xny+42y^2n=0 | | 5g+15=2g | | -4x^3-2x+1=0 | | 6x+38=14 | | 27u^2+54uv-21v^2=0 | | 1x-2y-3z=0 | | Y^2+4Y+11=0 | | (2x-3)(x^2-5x+3)=0 | | -8-3c=19 | | ln^2x+lnx=12 |

Equations solver categories